2022
DOI: 10.1038/s43016-022-00549-0
|View full text |Cite
|
Sign up to set email alerts
|

Time management governs climate resilience and productivity in the coupled rice–wheat cropping systems of eastern India

Abstract: India will need to produce 30% more wheat by 2050, and these gains must principally come from intensification in eastern India where low productivity is common. Through a dense network of on-farm surveys for the rice–wheat system in this region, we show that contemporary wheat sowing dates have a central influence on achieved and attainable yields, superseding all other crop management, soil and varietal factors. We estimate that untapped wheat production potential will increase by 69% with achievable adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…3 ). Although our models do not control for unobserved variables, agronomic studies in these systems have consistently shown that planting dates, fertilizer, varieties, soil types and especially irrigation are consistently the most important predictors for yield ( Devkota et al, 2021 ; McDonald et al, 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Although our models do not control for unobserved variables, agronomic studies in these systems have consistently shown that planting dates, fertilizer, varieties, soil types and especially irrigation are consistently the most important predictors for yield ( Devkota et al, 2021 ; McDonald et al, 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…population has some of the highest rates of malnutrition and rural poverty (TCI, 2022), coupled with some of the highest crop yield gaps in India (Jain et al, 2017;Pathak et al, 2003;TCI, 2022). Both private and public investments are working to close yield gaps through improved agronomic management, such as timely wheat planting (McDonald et al, 2022) and expanding the adoption of hybrid rice (Spielman, Ward, & Kolady, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Zero tillage, minimum tillage or use of happy seeder are alternatives to traditional tillage practices in rice-wheat cropping system ( Acharya et al., 2011 ). Zero tillage facilitates the sowing 10-15 days earlier which helps in escaping the terminal heat stress and results in yield gain by 10-25% in EGP ( Joshi et al., 2007c ; McDonald et al., 2022 ). Early sowing is effective in reducing SB, subjected to selection of suitable variety for early sowing as 1) the genotypes must have capacity to tolerate high temperature at early crop growth stage; 2) proper management of foliar blight diseases; as sometimes higher leaf bight incidence was observed upon early sowing due to high residual moisture and humidity ( Duveiller, 2004 ).…”
Section: Disease Management Strategiesmentioning
confidence: 99%